Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Microbial polyhydroxyalkanoate synthesis from field pea starch hydrolysate - Warren Blunt; Fang Huang; Christopher Doyle; Vinicio Vasquez; Trent C. Yang (Bioresource Technology Reports, 2025)

Broad-scale pesticide screening finds anticoagulant rodenticide and legacy pesticides in Australian frogs - Jodi J.L. Rowley; Andrew Symons; Christopher Doyle; Jane Hall; Karrie Rose; Laura Stapp; Damian C. Lettoof (Science of The Total Environment, 2024)

Persistent organic pollutants and trace elements detected in New Zealand fur seals (long-nosed fur seal; Arctocephalus forsteri) from New South Wales, Australia, between 1998 and 2019 - Jane Hall; Susan Bengtson Nash; Anil Gautam; Hannah Bender; Benjamin J. Pitcher; Hamish McCallum; Christopher Doyle (Science of The Total Environment, 2023)

The potential of Burkholderia thailandensis E264 for co-valorization of C5 and C6 sugars into multiple value-added bio-products - Warren Blunt; Catherine Blanchard; Christopher Doyle; Vinicio Vasquez; Mengwei Ye; Peter Adewale; Yali Liu; Krista Morley; Fanny Monteil-Rivera (Bioresource Technology, 2023)

Portable gas chromatography–mass spectrometry method for the in-field screening of organic pollutants in soil and water at pollution incidents - Denise Duff; Chris Lennard; Yarong Li; Christopher Doyle; Katelyn J. Edge; Ian Holland; Kevin Lothridge; Paul Johnstone; Paul Beylerian; Val Spikmans (Environmental Science and Pollution Research, 2023)
Environmental pollution incidents generate an emergency response from regulatory agencies to ensure that the impact on the environment is minimised. Knowing what pollutants are present provides important intelligence to assist in determining how to respond to the incident. However, responders are limited in their in-field capabilities to identify the pollutants present. This research has developed an in-field, qualitative analytical approach to detect and identify organic pollutants that are commonly detected by regulatory environmental laboratories. A rapid, in-field extraction method was used for water and soil matrices. A coiled microextraction (CME) device was utilised for the introduction of the extracted samples into a portable gas chromatography–mass spectrometry (GC–MS) for analysis. The total combined extraction and analysis time was approximately 6.5 min per sample. Results demonstrated that the in-field extraction and analysis methods can screen for fifty-nine target organic contaminants, including polyaromatic hydrocarbons, monoaromatic hydrocarbons, phenols, phthalates, organophosphorus pesticides, and organochlorine pesticides. The method was also capable of tentatively identifying unknown compounds using library searches, significantly expanding the scope of the methods for the provision of intelligence at pollution incidents of an unknown nature, although a laboratory-based method was able to provide more information due to the higher sensitivity achievable. The methods were evaluated using authentic casework samples and were found to be fit-for-purpose for providing rapid in-field intelligence at pollution incidents. The fact that the in-field methods target the same compounds as the laboratory-based methods provides the added benefit that the in-field results can assist in sample triaging upon submission to the laboratory for quantitation and confirmatory analysis.

Animal population decline and recovery after severe fire: Relating ecological and life history traits with expert estimates of population impacts from the Australian 2019-20 megafires - Michelle Ensbey; Sarah Legge; Chris J. Jolly; Stephen T. Garnett; Rachael V. Gallagher; Mark Lintermans; Dale G. Nimmo; Libby Rumpff; Ben C. Scheele; Nick S. Whiterod; John C.Z. Woinarski; Shane T. Ahyong; et al. (Biological Conservation, 2023)

The conservation impacts of ecological disturbance: Time‐bound estimates of population loss and recovery for fauna affected by the 2019–2020 Australian megafires - Sarah Legge; Libby Rumpff; John C. Z. Woinarski; Nick S. Whiterod; Michelle Ward; Darren G. Southwell; Ben C. Scheele; Dale G. Nimmo; Mark Lintermans; Hayley M. Geyle; Stephen T. Garnett; Brittany Hayward‐Brown; et al. (Global Ecology and Biogeography, 2022)
Aim After environmental disasters, species with large population losses may need urgent protection to prevent extinction and support recovery. Following the 2019–2020 Australian megafires, we estimated population losses and recovery in fire‐affected fauna, to inform conservation status assessments and management. Location Temperate and subtropical Australia. Time period 2019–2030 and beyond. Major taxa Australian terrestrial and freshwater vertebrates; one invertebrate group. Methods From > 1,050 fire‐affected taxa, we selected 173 whose distributions substantially overlapped the fire extent. We estimated the proportion of each taxon’s distribution affected by fires, using fire severity and aquatic impact mapping, and new distribution mapping. Using expert elicitation informed by evidence of responses to previous wildfires, we estimated local population responses to fires of varying severity. We combined the spatial and elicitation data to estimate overall population loss and recovery trajectories, and thus indicate potential eligibility for listing as threatened, or uplisting, under Australian legislation. Results We estimate that the 2019–2020 Australian megafires caused, or contributed to, population declines that make 70–82 taxa eligible for listing as threatened; and another 21–27 taxa eligible for uplisting. If so‐listed, this represents a 22–26% increase in Australian statutory lists of threatened terrestrial and freshwater vertebrates and spiny crayfish, and uplisting for 8–10% of threatened taxa. Such changes would cause an abrupt worsening of underlying trajectories in vertebrates, as measured by Red List Indices. We predict that 54–88% of 173 assessed taxa will not recover to pre‐fire population size within 10 years/three generations. Main conclusions We suggest the 2019–2020 Australian megafires have worsened the conservation prospects for many species. Of the 91 taxa recommended for listing/uplisting consideration, 84 are now under formal review through national processes. Improving predictions about taxon vulnerability with empirical data on population responses, reducing the likelihood of future catastrophic events and mitigating their impacts on biodiversity, are critical.

SMART Cables for Observing the Global Ocean: Science and Implementation - Bruce M. Howe; Brian K. Arbic; Jérome Aucan; Christopher R. Barnes; Nigel Bayliff; Nathan Becker; Rhett Butler; Laurie Doyle; Shane Elipot; Gregory C. Johnson; Felix Landerer; Stephen Lentz; et al. (Frontiers in Marine Science, 2019)

An Intracardiac Soft Robotic Device for Augmentation of Blood Ejection from the Failing Right Ventricle - Markus A. Horvath; Isaac Wamala; Eric Rytkin; Elizabeth Doyle; Christopher J. Payne; Thomas Thalhofer; Ignacio Berra; Anna Solovyeva; Mossab Saeed; Sara Hendren; Ellen T. Roche; Pedro J. del Nido; et al. (Annals of Biomedical Engineering, 2017)

Diffusion Tensor Tractography of the Cerebellar Peduncles in Prematurely Born 7-Year-Old Children - Eilon Shany; Terrie E. Inder; Sharon Goshen; Iris Lee; Jeffrey J. Neil; Christopher D. Smyser; Lex W. Doyle; Peter J. Anderson; Joshua S. Shimony (The Cerebellum, 2017)

A New MRI-Based Pediatric Subcortical Segmentation Technique (PSST) - Wai Yen Loh; Alan Connelly; Jeanie L. Y. Cheong; Alicia J. Spittle; Jian Chen; Christopher Adamson; Zohra M. Ahmadzai; Lillian Gabra Fam; Sandra Rees; Katherine J. Lee; Lex W. Doyle; Peter J. Anderson; et al. (Neuroinformatics, 2016)

Ecotoxicological Effects of an Arsenic Remediation Method on Three Freshwater Organisms—Lemna disperma, Chlorella sp. CE-35 and Ceriodaphnia cf. dubia - M. Azizur Rahman; Ben Hogan; Elliott Duncan; Christopher Doyle; Mohammad Mahmudur Rahman; T. V. Nguyen; Richard P. Lim; William Maher; Ravi Naidu; Rick Krassoi; S. Vigneswaran; Christel Hassler (Water, Air, & Soil Pollution, 2015)

Corrosion of metal roof materials related to volcanic ash interactions - Christopher Oze; Jim Cole; Allan Scott; Thomas Wilson; Grant Wilson; Sally Gaw; Samuel Hampton; Colin Doyle; Zhengwei Li (Natural Hazards, 2014)

A reduced reaction mechanism for the simulation in ethylene flare combustion - Helen H. Lou; Christopher B. Martin; Daniel Chen; Xianchang Li; Kyuen Li; Hitesh Vaid; Anjan Tula Kumar; Kanwar Devesh Singh; Doyle P. Bean (Clean Technologies and Environmental Policy, 2012)

Relative Precision of Inhaler Aerodynamic Particle Size Distribution (APSD) Metrics by Full Resolution and Abbreviated Andersen Cascade Impactors (ACIs): Part 2—Investigation of Bias in Extra-Fine Mass Fraction with AIM-HRT Impactor - Jolyon P. Mitchell; Mark W. Nagel; Cathy C. Doyle; Rubina S. Ali; Valentina I. Avvakoumova; J. David Christopher; Jorge Quiroz; Helen Strickland; Terrence Tougas; Svetlana Lyapustina (AAPS PharmSciTech, 2010)

Relative Precision of Inhaler Aerodynamic Particle Size Distribution (APSD) Metrics by Full Resolution and Abbreviated Andersen Cascade Impactors (ACIs): Part 1 - Jolyon P. Mitchell; Mark W. Nagel; Cathy C. Doyle; Rubina S. Ali; Valentina I. Avvakoumova; J. David Christopher; Jorge Quiroz; Helen Strickland; Terrence Tougas; Svetlana Lyapustina (AAPS PharmSciTech, 2010)

Natural Variation of Flowering Time and Vernalization Responsiveness in Brachypodium distachyon - Christopher J. Schwartz; Mark R. Doyle; Antonio J. Manzaneda; Pedro J. Rey; Thomas Mitchell-Olds; Richard M. Amasino (BioEnergy Research, 2010)

Landscape analysis and pattern of hurricane impact and circulation on mangrove forests of the Everglades - Thomas W. Doyle; Ken W. Krauss; Christopher J. Wells (Wetlands, 2009)

Water level observations in mangrove swamps during two hurricanes in Florida - Ken W. Krauss; Thomas W. Doyle; Terry J. Doyle; Christopher M. Swarzenski; Andrew S. From; Richard H. Day; William H. Conner (Wetlands, 2009)

The Effect of 17β-Estradiol on the Development of Modified Hemal Spines in Early–Life Stage Gambusia holbrooki - Christopher A. Rawson; Richard P. Lim; Michael St. J. Warne; Christopher J. Doyle (Archives of Environmental Contamination and Toxicology, 2006)

Periphyton nutrient limitation and nitrogen fixation potential along a wetland nutrient-depletion gradient - J. Thad Scott; Robert D. Doyle; Christopher T. Filstrup (Wetlands, 2005)

Sediment Dynamics in the Adriatic Sea Investigated with Coupled Models - Christopher Sherwood; Jeffrey Book; Sandro Carniel; Luigi Cavaleri; Jacopo Chiggiato; Himangshu Das; James Doyle; Courtney Harris; Alan Niedoroda; Henry Perkins; Pierre-Marie Poulain; Julie Pullen; et al. (Oceanography, 2004)

Stability in the historical pattern of genetic structure of Newfoundland cod (Gadus morhua) despite the catastrophic decline in population size from 1964 to 1994 - Daniel E. Ruzzante; Christopher T. Taggart; Roger W. Doyle; Doug Cook (Conservation Genetics, 2001)

Modeling submersed macrophyte growth in relation to underwater light climate: modeling approaches and application potential - Elly P. H. Best; Christopher P. Buzzelli; Steven M. Bartell; Richard L. Wetzel; William A. Boyd; Robert D. Doyle; Kym R. Campbell (Hydrobiologia, 2001)